Đánh giá kết quả sớm phẫu thuật điều trị chấn thương tuy - Liệt, Đỗ Hữu; Mỹ, Đoàn Tiến; Chí, Phạm Hữu Thiện; Thọ, Bùi An; Trí, Phan Minh; Khánh, Lê Công; Hưng, Nguyễn Phước; Tam, Nguyễn Đình; Toàn, Phạm Duy; Quốc, Trần Đình; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
A